2020
DOI: 10.1002/14651858.cd012196.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation for treating pressure ulcers

Abstract: Analysis 1.1. Comparison 1 Electrical stimulation (plus standard care) versus sham/no electrical stimulation (plus standard care), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 83 publications
1
45
0
2
Order By: Relevance
“…1) shows the number of studies identified, screened, assessed for eligibility, and included in the review, with reasons for exclusions at each stage [21]. There were 27 reviews included in the qualitative syntheses; nine for PI prevention [27][28][29][30][31][32][33][34][35], and 21 for PI treatment [28,31,34,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Three reviews [28,31,34], examined both PI prevention and treatment.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) shows the number of studies identified, screened, assessed for eligibility, and included in the review, with reasons for exclusions at each stage [21]. There were 27 reviews included in the qualitative syntheses; nine for PI prevention [27][28][29][30][31][32][33][34][35], and 21 for PI treatment [28,31,34,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Three reviews [28,31,34], examined both PI prevention and treatment.…”
Section: Study Selectionmentioning
confidence: 99%
“…Twenty-one reviews published between 2006 and 2020 included 178 studies [28,31,34,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], and 18,348 participants (range = 40 to 6963). Eleven reviews reported the GRADE assessments of the certainty of evidence for each outcome across included studies, judging them to be mostly low or very low quality [34,38,[40][41][42][43]45,49,[51][52][53]. Only three reviews reported moderate quality/certainty evidence [49,52,53].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heterogeneity was shown to be high in the studies included in both of these reviews, which also included at least one non-RCT [72,73]. An upcoming Cochrane review of electrical stimulation for treating PUs will further add to the evidence base for this intervention [79].…”
Section: 'Empty' Reviewsmentioning
confidence: 99%
“…A number of additional systematic reviews have been registered with the Cochrane Wounds Editorial Base, the protocols for which are currently in the process of being developed, or the reviews themselves undertaken [79][80][81][82][83][84][85] ( Table 3). In addition to these, protocols for other (non-Cochrane) systematic reviews have recently been published, which look specifically at interventions for PUs in people with SCI (e.g., self-management interventions to improve skin care for PU prevention [86]).…”
Section: Upcoming Reviewsmentioning
confidence: 99%